UPAYA MENINGKATKAN BAHASA RESEPTIF ANAK MENGGUNAKAN CERITA BERGAMAR DIGITAL DI TK PERTIWI BANGO - Apriliana, Fhenty Dias (Jurnal Visi Ilmu Pendidikan, 2025)
ABSTRACT  The problem of children's receptive language abilities in early childhood still needs to be improved. Formation of the character of early childhood's love of reading is less than optimal, words that are easy but difficult for children to read and pronounce. This problem stems from the lack of variety in the media used by teachers in the classroom and not appropriate to the students' developmental stages. Diversity in teaching strategies and resources used is lacking. So children have difficulty listening to what the teacher says.   The aim of this research is to describe the teacher's actions, as well as assess children's activities and the consequences of their language development in repeating what they hear in telling stories using richer vocabulary through storytelling methods using digital media. This research uses an action research design and qualitative methodology. There are four meeting sessions for the class. The research results showed that the teacher's efforts at the third meeting met the requirements very well. All children's activities at the fourth meeting were classified as active. At the fourth meeting, the child's development results were in the very good development (BSB) category with an assessment of 100%. The findings of this research can be a guide and source of information in choosing a learning model.